The Effect Of Gdp, Fdi, Number Of Motor Vehicles, Industrial Growth, And Renewable Energy On Co2 In Asean (Journal of Namibian Studies : History Politics Culture, 2024)
This study aims to analyze and determine the effect of GDP, FDI, number of motor vehicle, industrial growth, and renewable energy on carbon dioxide emissions in ASEAN countries. This study uses panel data from 2010 - 2020 using the Random Effect Model (REM). The dependent variable used is the level of carbon dioxide emissions and the independent variables include GDP, FDI, number of motor vehicle, industrial growth, and renewable energy. The results in this study showed that GDP, industrial growth, and number of motor vehicle had a positive and significant effect, while FDI had a positive insignificant effect to the CO2 emissions in ASEAN countries. Renewable energy had a negative and significant effect related to the CO2 emissions.